(untitled) (Eurasian Journal of Philology Science and Education, 2018)
The article is devoted to the exposure of linguistic features of a parable text. The term «parable» is polysemantic. The authors refer to the definition of parable, given by S. Averentsev as most entire and exact. The aim of the article is to describe the methods of syntactic organization of author’s parable on the basis of a parable text by V. Rasputin. The topicality of the given research work is explained by the fact that studying the syntax of a creative writer is a problem, where the linguistic and aesthetic aspects bind together. Syntax is an important part of a text. The writer’s individual style is observed through the sentence structure, its stretch, the ways of segmentation, as well as through the sequences of sentences. The syntax analysis of Rasputin’s parable shows that it requires a symbolic depth and versatility. Rasputin’s parable contains some hidden moral potential to acquire which readers need have some intellect and brain work efforts.